Models of Coupled Settlement and Habitat Networks for Biodiversity Conservation: Conceptual Framework, Implementation and Potential Applications - van Strien, Maarten J.; Axhausen, Kay W.; Dubernet, Ilka; Guisan, Antoine; Grêt-Regamey, Adrienne; Khiali-Miab, Amin; Ortiz-Rodríguez, Damian O.; Holderegger, Rolf (Frontiers in Ecology and Evolution, 2018)
Worldwide, the expansion of settlement and transport infrastructure is one of the most important proximate as well as ultimate causes of biodiversity loss. As much as every modern human society depends on a network of settlements that is well-connected by transport infrastructure (i.e. settlement network), animal and plant species depend on networks of habitats between which they can move (i.e. habitat networks). However, changes to a settlement network in a region often threaten the integrity of the region’s habitat networks. Determining plans and policy to prevent these threats is made difficult by the numerous interactions and feedbacks that exist between and within the settlement and habitat networks. Mathematical models of coupled settlement and habitat networks can help us understand the dynamics of this social-ecological system. Yet, few attempts have been made to develop such mathematical models. In this paper, we promote the development of models of coupled settlement and habitat networks for biodiversity conservation. First, we present a conceptual framework of key variables that are ideally considered when operationalising the coupling of settlement and habitat networks. In this framework, we first describe important network-internal interactions by differentiating between the structural (i.e. relating to purely physical conditions determining the suitability of a location for living or movement) and functional (i.e. relating to the actual presence, abundance or movement of people or other organisms) properties of either network. We then describe the main one-way influences that a settlement network can exert on the habitat networks and vice versa. Second, we give several recommendations for the mathematical modelling of coupled settlement and habitat networks and present several existing modelling approaches (e.g. habitat network models and land-use transport interaction models) that could be used for this purpose. Lastly, we elaborate on potential application of models of coupled settlement and habitat networks in the development of complex network theory, in the assessment of system resilience and in conservation, transport and urban planning. The development of coupled settlement and habitat network models is important to gain a better system-level understanding of biodiversity conservation under a rapidly urbanising and growing human population.